Analisis Bahaya Bencana Gempa Bumi di Wilayah Kabupaten Pesisir Selatan - Farhan, Adam Muchammad; Edial, Helfia (YASIN, 2024)
This study aims to determine the earthquake hazard levels in Pesisir Selatan Regency, West Sumatra Province, by identifying the Peak Ground Acceleration (PGA) values and the distribution of earthquake hazard levels. The type of research used is quantitative descriptive analysis and spatial analysis. The method employed in this study is Probabilistic Seismic Hazard Analysis (PSHA). To determine the Peak Ground Acceleration values, parameters such as earthquake location, occurrence time, and earthquake magnitude are used. For determining the earthquake hazard distribution, data on Ground Amplification Factor (GAF) is utilized. The results of this study show that the distribution of Peak Ground Acceleration in the study area ranges from 0.17 g to 0.93 g. The value of 0.17 g is found in Koto XI Tarusan District, while the highest value is observed in Silaut District. Additionally, the distribution of earthquake hazard levels shows that areas with low hazard level cover 697.04 km², moderate hazard level covers 4150.49 km², and high hazard level covers 1201.81 km². This study provides earthquake hazard maps that can be used for mitigation and planning in the region.